Developing resilient design criteria for evacuation centre / Aainaa Suhardi, Ismail Samsuddin and Dzulkarnaen Ismail - Suhardi, Aainaa; Samsuddin, Ismail; Ismail, Dzulkarnaen (Universiti Teknologi MARA, Perak, 2023)
Schools and community halls are frequently chosen as disaster evacuation centres during difficult flood incidences. However, the buildings' existing designs and facilities are designed for their respective uses and are inefficient for disaster relief. Thus, the buildings' suitability as disaster evacuation centres is in doubt. It is therefore recommended to apply the Multidisciplinary Centre for Earthquake Engineering Research, or MCEER 4R’s Resilience Framework, to investigate the centres' resilience. It integrates four primary qualities to make a more disaster-resilient centre. These are robustness, redundancy, resourcefulness, and rapidity. The research method for the development of criteria is document analysis, which is used to collect qualitative data, which includes shelter design considerations, space provisions in a disaster evacuation centre, and resilience properties. Various official documents on disaster management, shelter guidelines, and resilience frameworks were used to compile this research. These documents attribute the current design standards used in a disaster evacuation centre and inform researchers that each design standard includes embedded resilience features. The findings of the document analysis approach will be used to understand key design issues and resilience ideas. Before identifying the essential design standards through the content validation process, this becomes an initial list of shelter design standards acquired from official shelter guidelines. The findings will be presented in a disaster evacuation centre context, emphasising the four design domains with built-in resilience: site planning, spatial layout, existing design, and existing construction. The investigation continued with transforming the design variables into resilient design measures, synthesising the resilience ideas gathered from the shelter guidelines. A tabulation of four resilience categories was put together to see the overall resilience design pattern in disaster evacuation centres. This study aimed to develop a practical design framework that included design guidelines and resilience indicators for improving the existing design and space planning of the disaster evacuation centre buildings. As a result, the facilities can be enhanced to provide a resilient, more secure, comfortable, and practical environment for flood victims and rescuers.